2016
DOI: 10.1016/j.rmed.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

A 12-year prognosis of adult-onset asthma: Seinäjoki Adult Asthma Study

Abstract: During a 12-year follow-up, remission of adult-onset asthma was rare occurring in only 3% of patients. The majority of patients (66%) presented either with uncontrolled or partially controlled asthma. This study is registered at ClinicalTrials.gov with identifier number NCT02733016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 33 publications
4
104
0
Order By: Relevance
“…The findings are clinically significant, since remission rate in adult onset asthma is low [7] and most patients suffer from asthma for decades. The linearity of the effect of physical activity on lung function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings are clinically significant, since remission rate in adult onset asthma is low [7] and most patients suffer from asthma for decades. The linearity of the effect of physical activity on lung function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were treated and monitored according to Finnish Asthma Program guidelines [19] either in the specialized care or in primary care. The collection of research data has been previously reported [7,9,10,20]. At diagnosis, data was collected on lung function, blood eosinophils, the initial pharmacotherapy, and asthma symptoms by Airways Questionnaire 20 (AQ20) [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review has shown that adult-onset asthma has a worse prognosis and a lower response to standard asthma treatment than childhood-onset asthma [8]. In a 12-year follow-up study of adult-onset asthma elevated BMI at baseline, smoking and current allergic or persistent rhinitis predicted uncontrolled asthma, and elevated blood eosinophils and good lung function (FEV1) at baseline protected from uncontrolled asthma [9]. Remission rates vary widely due to varying definitions of asthma and observation time but generally early-onset asthma has a substantially higher remission rate than late-onset asthma [10].…”
Section: Introductionmentioning
confidence: 99%
“…11 Briefly, asthma was diagnosed by a specialized respiratory physician during the period 1999 to 2002 on the basis of typical clinical symptoms and confirmed by objective lung function measurements. 11,12 The main diagnostic features of asthma in each cluster are presented in Table E1 in this article's Online Repository at www.jaci-inpractice.org. Smokers and patients with comorbidities were not excluded.…”
Section: Patients and Study Designmentioning
confidence: 99%